Cognitive impairment in Chinese neuromyelitis optica. (December 2015) - Zhang, N; Li, YJ; Fu, Y; Shao, JH; Luo, LL; Yang, L; Shi, FD; Liu, Y
Background: Cognitive dysfunction is frequently seen in neuromyelitis optica (NMO). However, the features and influencing factors of cognitive impairment of Chinese NMO patients are unclear. Objective: To investigate the patterns of cognitive impairment in Chinese NMO patients, and correlate the neuropsychiatric scores with clinical and MRI parameters. Methods: Thirty-six Chinese NMO patients, and 30 sex and age-matched healthy controls were recruited with extensive neuropsychological assessments, using the modified Minimal Assessment of Cognitive Function in MS (MACFIMS). The demographic and clinical characteristics as well as MRI parameters were compared between cognitively impaired (CI) and cognitively preserved (CP) patients. Results: NMO patients were significantly impaired in the Paced Auditory Serial Addition Task ( P <0.05), the Symbol Digit Modalities Test ( P <0.001), the California Verbal Learning Test-Second Edition ( P <0.05), the Brief Visuospatial Memory Test-Revised ( P <0.05) and semantic fluency ( P <0.001). Only lower education level was associated with cognitive dysfunction in NMO (odds ratio: 0.57, P <0.05). There were no significant differences of MRI parameters regarding white matter (WM) lesions, grey matter and WM brain volume between CI and CP patients. Conclusions: Chinese NMO patients particularly demonstrated cognitive impairment in information processing speed, executive function and memory. Lower education level was the main factor contributing to cognitive impairment in NMO.